Hydroxyapatite Chitosan Gradient Pore Scaffold Activates Oxidative Phosphorylation Pathway to Induce Bone Formation - Zeliang Zhang; Wei Shang; Lisong Lin (Frontiers in Bioscience-Landmark)
Background: In this study, we prepared a porous gradient scaffold with hydroxyapatite microtubules (HAMT) and chitosan (CHS) and investigated osteogenesis induced by these scaffolds. Methods: The arrangement of wax balls in the mold can control the size and distribution of the pores of the scaffold, and form an interconnected gradient pore structure. The scaffolds were systematically evaluated in vitro and in vivo for biocompatibility, biological activity, and regulatory mechanisms. Results: The porosity of the four scaffolds was more than 80%. The 50% and 70% HAMT-CHS scaffolds formed an excellent gradient pore structure, with interconnected pores. Furthermore, the 70% HAMT-CHS scaffold showed better anti-compressive deformation ability. In vitro experiments indicated that the scaffolds had good biocompatibility, promoted the expression of osteogenesis-related genes and proteins, and activated the oxidative phosphorylation pathway to promote bone regeneration. Eight weeks after implanting the HAMT-CHS scaffold in rat skull defects, new bone formation was observed in vivo by micro-computed tomographic (CT) staining. The obtained data were statistically analyzed, and the p-value < 0.05 was statistically significant. Conclusion: HAMT-CHS scaffolds can accelerate osteogenesis in bone defects, potentially through the activation of the oxidative phosphorylation pathway. These results highlight the potential therapeutic application of HAMT-CHS scaffolds.